2017
DOI: 10.1016/j.algal.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-study analysis of factors affecting algae cultivation in recycled medium for biofuel production

Abstract: Current high costs of commercial-scale algal biofuel production prevent its widespread use as a renewable fuel source. One cost-saving approach is the reuse of algae cultivation water after biomass harvesting, which reduces water pumping and treatment costs. However, dissolved compounds, cell debris, and microorganisms remaining in the water could affect subsequent algae generations. Previous studies demonstrate a variety of effects of recycled medium on algae growth, yet their results have not been collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 118 publications
(125 reference statements)
1
20
0
Order By: Relevance
“…Algae growth responses observed here are broadly consistent with the observation that growth success in reused medium is taxa-dependent, as shown in a meta-analysis (Loftus and Johnson, 2017). This genus-level specificity appears to be true even within major groups of algae, as within the diatoms Staurosira sp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Algae growth responses observed here are broadly consistent with the observation that growth success in reused medium is taxa-dependent, as shown in a meta-analysis (Loftus and Johnson, 2017). This genus-level specificity appears to be true even within major groups of algae, as within the diatoms Staurosira sp.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have tested how reused medium affects algae growth using a variety of algae taxa, harvesting methods, and growth conditions. These studies revealed diverse growth responses ranging from inhibition to stimulation, though most experiments found no substantial effects caused by reused medium (Loftus and Johnson, 2017). One factor that accounted for the wide variety of growth responses was algae taxa.…”
Section: Introductionmentioning
confidence: 99%
“…However, microorganisms are known to have preferred organic carbon sources, and different types of organic carbon are available depending on the environment (Brückner and Titgemeyer, 2002;Abreu et al, 2012). In addition, some studies suggest that the medium obtained by culturing certain microbial species can be recycled (Loftus and Johnson, 2017;Wang et al, 2018;Li et al, 2019). Therefore, it is expected that there has been no competition to impede growth in the use of organic carbon sources among species in conditions in which higher biomass could be produced (Loftus and Johnson, 2017;Wang et al, 2018;Li et al, 2019).…”
Section: Co-culture Effects On Biomass Productivity and Lipid Qualitymentioning
confidence: 99%
“…In addition, some studies suggest that the medium obtained by culturing certain microbial species can be recycled (Loftus and Johnson, 2017;Wang et al, 2018;Li et al, 2019). Therefore, it is expected that there has been no competition to impede growth in the use of organic carbon sources among species in conditions in which higher biomass could be produced (Loftus and Johnson, 2017;Wang et al, 2018;Li et al, 2019). Furthermore, improved lipid productivity may be related to lipid accumulation due to nutrient starvation (Chu et al, 2020;Poh et al, 2020).…”
Section: Co-culture Effects On Biomass Productivity and Lipid Qualitymentioning
confidence: 99%
“…The effects of water reuse on algae growth are different across algae taxa [ 6 ]. The most researched taxa are green algae, diatoms, cyanobacteria, haptophytes, eustigmatophytes, chrysophytes, and xanthophytes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%